Inflation and Coal Prices: Analyzing Their Influence on Mining Sector Stock Returns in Indonesia - Putra, Johny Sumarna; Motameni, Mani (PT Aksara Indo Rajawali, 2024)
This research examines the influence of coal prices and inflation on mining sector stock returns in the short and long-term using monthly data from the period January 2009 – December 2020. Data analysis in this study used the Autoregressive Distributed-Lag (ARDL). Based on the results, it can be concluded that in the short term, inflation exerts a negative and significant impact on stock returns in the mining sector. Conversely, coal prices do not influence stock returns in this sector. The long-term findings mirror this pattern, demonstrating that inflation continues to have a negative and significant effect on mining sector stock returns, while coal prices remain uninfluential. Policymakers, investors, and financial actors are advised to consider energy related objectives and developments, particularly in the coal sector, as critical indicators for financial decision-making. It is also important to consider that the timeframe chosen for decision making will significantly impact investment performance, as any variation in time can greatly influence the results. It acknowledges that other factors, such as the Rupiah exchange rate, interest rates, and additional variables, also potentially affect these returns. It is recommended that future studies expand the scope of investigation to include these additional factors to attain a more thorough understanding of the determinants of stock returns in the mining sector.